Environmental assessment of heavy metals in the soil and Trifolium pratense L. - Довгопола, К. А. (Problems of Environmental Biotechnology, 2016)
The results of the study of heavy metals in soils and red clover, which were collected in the territory adjacent to the airfield Nizhyn Chernihiv region. Established technological factors concentrations of heavy metals in soil samples and intensity of migration of pollutants from soil to plants using biological absorption coefficient.